Angiomyxoma of the Lower Eyelid with Orbital Extension: A Rare Entity and Review of Literature - Agrawal, Sahil; Deora, Aarush; Modaboyina, Sujeeth; Das, Deepsekhar; Bajaj, Mandeep Singh; Sen, Seema (Annals of Pathology and Laboratory Medicine, 2021)
A 60-year-old male sought medical advice for painless progressive swelling in the left eye associated with protrusion of the eyeball and diminution of vision for the past 6 months. A computed tomography scan was done which revealed a heterogeneous lesion in the inferotemporal orbit lying close to the globe without any bony erosions or intracranial extension. Incisional biopsy revealed spindle or stellate cells in a myxoid matrix with abundant thin-walled vessels. On Immunohistochemistry, the tumour was positive for vimentin and SMA. It was negative for Desmin and S-100. A diagnosis of superficial angiomyxoma of the eyelid with orbital extension was thus made. Surgical excision under general anaesthesia was planned and the mass removed in toto. The histopathological examination of the same revealed findings similar to the incision biopsy. The patient is being followed up with no recurrences till date.